Comparison of ONIX simulation results with experimental data from the BATMAN testbed for the study of negative ion extraction. (19th August 2016) - Mochalskyy, Serhiy; Fantz, Ursel; Wünderlich, Dirk; Minea, Tiberiu
Abstract: The development of negative ion (NI) sources for the ITER neutral beam injector is strongly accompanied by modelling activities. The ONIX (Orsay Negative Ion eXtraction) code simulates the formation and extraction of negative hydrogen ions and co-extracted electrons produced in caesiated sources. In this paper the 3D geometry of the BATMAN extraction system, and the source characteristics such as the extraction and bias potential, and the 3D magnetic field were integrated in the model. Calculations were performed using plasma parameters experimentally obtained on BATMAN. The comparison of the ONIX calculated extracted NI density with the experimental results suggests that predictive calculations of the extraction of NIs are possible. The results show that for an ideal status of the Cs conditioning the extracted hydrogen NI current density could reach 30 mA cm −2 at 10 kV and 20 mA cm −2 at 5 kV extraction potential, with an electron/NI current density ratio of about 1, as measured in the experiments under the same plasma and source conditions. The dependency of the extracted NI current on the NI density in the bulk plasma region from both the modeling and the experiment was investigated. The separate distributions composing the NI beam originating from the plasma bulk region and the PG surface are presented for different NI plasma volume densities and NI emission rates from the plasma grid (PG) wall, respectively. The extracted current from the NIs produced at the Cs covered PG surface, initially moving towards the bulk plasma and then being bent towards the extraction surfaces, is lower compared to the extracted NI current from directly extracted surface produced ions.